Influence of tree canopy on N2 fixation by pasture legumes and soil rhizobial abundance in Mediterranean oak woodlands. - Carranca, C.; Castro, I. V.; Figueiredo, N.; Redondo, R.; Rodrigues, a R. F.; Saraiva, I.; Maricato, R.; Madeira, M. a V. (The Science of the total environment, 2015)
Symbiotic N2 fixation is of primordial significance in sustainable agro-forestry management as it allows reducing the use of mineral N in the production of mixed stands and by protecting the soils from degradation. Thereby, on a 2-year basis, N2 fixation was evaluated in four oak woodlands under Mediterranean conditions using a split-plot design and three replicates. (15)N technique was used for determination of N2 fixation rate. Variations in environmental conditions (temperature, rainfall, radiation) by the cork tree canopy as well as the age of stands and pasture management can cause great differences in vegetation growth, legume N2 fixation, and soil rhizobial abundance. In the present study, non-legumes dominated the swards, in particular beneath the tree canopy, and legumes represented only 42% of total herbage. A 2-fold biomass reduction was observed in the oldest sown pasture in relation to the medium-age sward (6tDWha(-1)yr(-1)). Overall, competition of pasture growth for light was negligible, but soil rhizobial abundance and symbiotic N2 fixation capacity were highly favored by this environmental factor in the spring and outside the influence of tree canopy. Nitrogen derived from the atmosphere was moderate to high (54-72%) in unsown and sown swards. Inputs of fixed N2 increased from winter to spring due to more favorable climatic conditions (temperature and light intensity) for both rhizobia and vegetation growths. Assuming a constant fixation rate at each seasonal period, N2 fixation capacity increased from about 0.10kgNha(-1) per day in the autumn-winter period to 0.15kgNha(-1) per day in spring. Belowground plant material contributed to 11% of accumulated N in pasture legumes and was not affected by canopy. Size of soil fixing bacteria contributed little to explain pasture legumes N.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 25460942
Keywords: Above and belowground organ; Agro forestry system; Cutting frequency; light; Quercus Suber L

Analisi strutturale e caratterizzazione della necromassa in sugherete della Calabria - Barreca, L.; Marziliano, P. A.; Menguzzato, G.; Scuderi, A. (iForest - Biogeosciences and Forestry, 2010)
The cork forests are one the most interesting forest ecosystems in the Mediterranean area. Their distribution and ecological characteristics have undergone a significant transformation after the significant changes following the development and establishment of agricultural crops. Currently, only a few stands, which survive in hard to reach places, prove the wide spread distribution of this species was also in the recent past. This study describes the stand structure of some cork forests in Calabria region (southern Italy). In order, to characterize the vertical structure Latham index has been applied, while for the description of the horizontal distribution NBSI group indices has been used. Detailed surveys on dead wood were also conducted determining the occurring volume and its decay stage according to the decay classes system proposed by Hunter. The aim of this study is to provide guidelines for sustainable management of cork forests, improving and promoting the structural complexity and functional efficiency of these forest stands.
The following values have no corresponding Zotero field: pub-location: Dipartimento Gestione dei Sistemi Agrari e Forestali (GESAF), Universit degli studi Mediterranea di Reggio Calabria, Localit Feo di Vito, I-89060 Reggio Calabria (Italia) publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Dead Wood; Quercus Suber L; Stand Structure; Structural Index; Sustainable Forest Management

Estudio y caracterización de las masas de alcornoque de la provincia de León - FERNÁNDEZ-MANSO, A. A.; SARMIENTO MAILLO, L. A.; EZQUERRA BOTICARIO, F. J.; COBOS MIGUEL, T.; GARCÍA FERNÁNDEZ-MIRANDA, M. (V Congreso Forestal Español, 2009)
La falta de estudios sobre los alcornocales de la provincia de León hace que se desconozcan aspectos tan relevantes para su gestión sostenible como su distribución espacial, su estructura y dinámica o su estado de regeneración. A pesar de que algunos de los alcornocales leoneses son periódicamente descorchados no podemos hablar de una producción importante en términos económicos. Su importancia radica en sus valores ecológicos y culturales. El presente trabajo inventaría y analiza las 1.945,09 ha de alcornocal presente en la provincia de León localizados en su totalidad entre las comarcas de El Bierzo y la Cabrera. El objetivo del trabajo es obtener la información relevante de cara a la toma de decisiones en relación con las medidas de gestión más adecuadas para la especie. El trabajo presenta la localización geográfica y descripción ecológica de las masas de alcornocal, analiza su estructura y dinámica y estudia los usos actuales para prever su viabilidad futura.
The following values have no corresponding Zotero field: periodical: V Congreso Forestal Español pub-location: Avila
Keywords: el bierzo; estructura y dinámica forestal; Quercus Suber L

The relationship between cork oak growth patterns and soil, slope and drainage in a cork oak woodland in Southern Portugal - Costa, Augusta; Madeira, Manuel; Oliveira, Ângelo Carvalho (Forest Ecology and Management, 2008)
The inﬂuence of soil type, slope and drainage on tree growth patterns (density, tree size, crown canopy cover and cork yield) was assessed in a cork oak montado, located in Central-western Portugal, based on a GIS approach followed by ﬁeld survey. Five soil groups, that is, Arenosols, Regosols, Podzols, Luvisols and Gleysols, combined in three slope classes (ﬂat, undulating and steep) under two different hydromorphic conditions (normal or deﬁcient) were compared based on ﬁve cork oak stand parameters using ANOVA and PCA tests. The results showed a clear inﬂuence of soil type on cork oak growth patterns (cork yield, basal area, number of trees per hectare, crown canopy cover and circumference at breast height). In Arenosols all parameters showed maximum values and, in contrast, in Gleysols were found the minimum values. For instance, the average of the annual cork production for Gleysols (153 kg ha 1 year 1 ) was only 70% of the expected annual cork production of Arenosols (219 kg ha 1 year 1 ) and the average exploited tree density decreased from 56 trees ha 1 in Arenosols to 44 trees ha 1 in Gleysols, for an average exploited tree density of 53 trees ha 1 for the study area. Slope also seems to inﬂuence the cork oak growth patterns, as signiﬁcant statistical differences were found for cork oak growth parameters between slope classes: steep slopes decreased the cork production, the tree size (circumference at breast height) and the tree density. An overall PCA test showed that three main soil groups could be identiﬁed: (i) Arenosols and Podzols; (ii) Regosols and (iii) Luvisols and Gleysols, showing that the former, which could allow the tree root development, have a positive inﬂuence on the cork oak growth. A two-way analysis of variance, for soil type and slope, showed that the cork yield and the exploited tree density are clearly affected by these two factors interaction.
Keywords: cork yield; drainage; montado; Quercus Suber L; slope; Soil; tree density

The organosolv fractionation of cork components - Cordeiro, N.; Neto, C. P.; Rocha, J.; Belgacem, M. N.; Gandini, A. (HOLZFORSCHUNG, 2002)
Extractive-free cork from Quercus suber L. was submitted to organosolv fractionation and the effects of different process variables, such as ethanol/water ratio, temperature, time and the presence of acidic or alkaline catalysts, were studied. The variation of the relative proportions of extracted components, as a function of the processing conditions, could thus be established. Whereas the addition of 0.1 M acetic acid only increased the yield of extracted materials from about 15 to 23 %, the use of sodium hydroxide, at the same concentration, produced a jump to 76 %. In the case of the alkaline organosolv fractionation. an increase in process temperature, time and catalyst concentration led to an increase in the extraction yield, although in some cases this increase did not follow a sustained trend, as in the case of reaction time. Increasing the ethanol/water ratio led to a higher selectivity in favour of suberin extraction. Residual cork from different organosolv processes was characterised by FTIR and C-13 solid-state NMR. The latter technique provided some valuable information about both process selectivity and cork morphology, particularly with respect to the positioning of suberin macromolecules in the cell wall.
The following values have no corresponding Zotero field: pub-location: GENTHINER STRASSE 13, D-10785 BERLIN, GERMANY publisher: WALTER DE GRUYTER & CO
Keywords: C-13 NMR; Cork; ethanol/water extraction; FTIR; organosolv fractionation; Quercus Suber L; suberin

Identificação e Quantificação por DAD-HPLC, da Fracção Fenólica Contida em Folhas de Quercus suber L. - Evaristo, Isabel Maria; Leitão, Maria Cecília (Silva Lusitana, 2001)
In this study, an analytical method has been developed for the determination of phenolic compounds since they are related with disease and pests plant resistance mechanisms. The components of the hydrolysed extract (gallic acid, ellagic acid, catechin, epicatechin, caffeic acid, p-coumaric acid and ferulic acid) have been resolved and identified by DAD-HPLC based on their retention times and spectral data. For quantifications, the external standard method was used.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: avoir un rôle important; caffeic acid; car ces; catechin; dans la présente étude; défense des; des feuilles de chêne; détermination des composés phénoliques; ferulic acid; gallic acid; liège; méthode analytique pour la; on a developpé une; p-coumaric acid; Quercus Suber L; résumé; substances sont susceptibles d; sur les mécanismes de

Propagação Vegetativa por Estacaria do Sobreiro (Quercus suber L.) - Cordeiro, Sonia; Moreira, Carmen; Ferreira, R. P.; Carvalho, J. P. F.; Pinto, T. M. S.; Pereira, J. M. G. Torres (Silva Lusitana, 2001)
The PAMAF-IED 8110 (1997-2000) project, was used to verify the rhizogenic capacity of Quercus suber, throughout the study of rhizogenic behaviour of different kinds of propagule considering several rooting factors. Due to the preliminary state of statistical data analysis, these conclusions are at an early stage, consisting only in first indications to a later definition of the best combination of "propagule x rooting factors"
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: propagule; Quercus Suber L; rooting factors

Relations entre la qualité du liège, sa composition minérale et la composition minérale des feuilles du chêne-liège (Quercus suber L.) - Courtois, Michèle; Masson, Philippe (Ann. For. Sci., 1999)
Relationships between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak (Quercus suber L.). The aim of this work is to set up a relationship between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak. The mineral contents of both leaves and cork were identified for a range of elements (nitrogen, phosphorus, potassium, calcium, magnesium, iron, copper, zinc and manganese). The quality of the cork was evaluated by experts in the cork industry on the basis of visual assessment of cork stoppers resulting from each tree. A study of correlations between the cork inorganic contents and the quality of cork demonstrates that, among those measures, only the potassium content of cork is related to the cork quality. The cork quality seems to be independent of the leaf inorganic content, which is held to be an indicator of the cork-oak mineral nutrition. (© Inra/Elsevier, Paris.)
Keywords: Cork; inorganic content; leaf; Quality; Quercus Suber L

Influence of 50 Hz electromagnetic fields on recurrent embryogenesis and germination of cork oak somatic embryos - Celestino, Cristina; Picazo, M. L. (Plant cell, tissue and …, 1998)
Plant tissue culture techniques are carried out under environmentally controlled conditions in phytotrons. However, electric components of phytotrons generate electromagnetic ﬁelds that may act as a environmental factor inﬂuencing plant growth and morphogenesis. Isolated somatic embryos of Quercus suber, picked from embryogenic lines, were chronically exposed to a 50 Hz and 15 µT electromagnetic ﬁeld generated in a Helmholtz-coil system for 8 weeks, in order to examine if the extremely low frequency (ELF) magnetic ﬁeld (MF) affected the morphogenic behaviour of embryogenic cultures during recurrent embryogenesis. Germination of somatic embryos from genotype G7.1 was carried out under the same electromagnetic ﬁeld, and also under conditions in which the local geomagnetic ﬁeld was suppressed. The ELF MF did not inﬂuence the growth of embryogenic clumps of the assayed genotypes, but reduced the number of detachable embryos produced by genotype G3.27. The ELF MF did not modify the percentages of germination or plant formation of somatic embryos. However, somatic embryos had better germination when cultured under the suppressed geomagnetic ﬁeld condition.
Keywords: bioelectromagnetism; elf magnetic fields; germination; Quercus Suber L; Somatic embryogenesis; tissue culture

Rhythmic growth rings of wood and their relationship with the foliage in oak seedlings grown in a favourable environment - MANSOUR, A.; de FAŸ, E. (Annals of botany, 1998)
{{The anatomy of wood was studied in Quercus robur L. and Quercus suber L. seedlings exhibiting 3±8 units of extension, each with a tier of photosynthesizing leaves in their upper parts, generated as the result of rhythmic shoot growth under favourable conditions. At all the axis levels examined (i.e. the base of each of the diﬀerent units of extension, four other equidistant levels within the ®rst unit of extension and the upper part of the taproot), the wood displayed rings when treated with Wiesner reagents. This indicated cinnamaldehyde groups present in lignins. No rings appeared when the Mau$le reaction was used for speci®c detection of syringyl subunits in lignins. A trend towards a periodical arrangement of xylem parenchyma bands was also found when sections were treated with I # }KI. The number of rings coincided with the number of leaf tiers above the level of measurement, and did not vary inside the ®rst unit of extension. Thus, the rings are called rhythmic growth rings. In sections of the ®rst and the second units of extension, and in the taproot, the area and width of a given rhythmic growth ring were highly correlated with the total area of leaves present above the level of measurement at the presumed time of growth ring formation. Moreover, stem diameter at the base of the units of extension was highly correlated with the leaf area above. These results indicate that diﬀerentiation of xylem, particularly its ligni®cation, varies rhythmically in oak seedlings. They imply that wood production is linked to the photosynthesizing and}or transpiring area of the plant. Thus, during a growth cycle of Q. robur and Q. suber seedlings, there appears to be integration of the primary metabolic activities with the laying down of rhythmic growth rings
Keywords: allometric relationship; juvenile wood; leaf area; lignification; oak seedling; periodic structure; quercus robur l; Quercus Suber L; rhythmic growth ring; unit of extension

Volatile compounds produced by microorganisms isolated from cork - Caldentey, Paloma; Fumi, Maria Daria; Mazzoleni, Valeria; Careri, Maria (Flavour and Fragrance Journal, 1998)
Microorganisms present on cork (i.e. the reproduction bark of Quercus suber L.) can produce odorous compounds aecting the quality of cork stoppers. This work aims to contribute to the study of the correlation between microbial growth and formation of volatile compounds in the cork. Dierent strains of microorganisms were cultivated on both malt extract and cork, and the odour of the culture was described by a panel. The volatile compounds were isolated directly from the culture media by a dynamic headspace technique followed by adsorption on to Tenax traps. The volatiles were identi®ed by GC±MS: 63 substances were identi®ed in malt extract cultures, mainly consisting of carbonyl compounds (16), alcohols (16), and sesquiterpenes (13). Cultures on cork produced only 12 volatile compounds, more than half being sesquiterpenes. Sensory evaluation con®rmed that cork is an unfavourable culture medium if compared with malt extract.
Keywords: Cork; microbial growth; Quercus Suber L; volatile components

Nutrient content and seasonal fluctuations in the leaf component of coark-oak (Quercus suber L.) litterfall - Robert, B.; Caritat, A.; Bertoni, G.; Vilar, L.; Molinas, M. (Plant Ecology, 1996)
Nutrient content and seasonality of the leaf component in cork-oak litterfal were studied over a two year period in two cork-oak forest sites differing in biomass and edaphic condition in the north-eastern Iberian peninsula. Fallen senescent leaves compared to young leaves showed higher non-mobile nutrient concentrations and lower mobile nutrient concentrations, specially P, N, K, and Mg. At both sites, seasonal fluctuations affected both leaf production and leaf mineral content. The maximum leaf fall period correspond to the start of the vegetative growth and to the lowest N and P concentration in the falling leaves. The opposite was true for the winter, when litterfal was minimal and N and P content in falling leaves was at a maximum. The comparison between falling leaves and canopy leaves suggests that the analysis of fallen leaves can be a useful measure of N and P nutrition in cork-oak. We found site dependent differences in nutrient content and nutrient remobilization. In comparison with Q. ilex, although litter production was in the same range, nutrient retranslocation was greater for Q. suber.
Keywords: litterfall; nutrient return; nutrients in leaves; Quercus Suber L; retranslocation; seasonal trends

Photoinhibition in cork-oak leaves under stress: influence of the bark-stripping on the chlorophyll fluorescence emission inQuercus suber L. - Werner, Christiane; Correia, O. (Trees-Structure and Function, 1996)
Quercus suber is the primary source for industrial cork and becomes bark-stripped every 9 – 10 years. Recurring cork extraction is a major stress factor and the large water loss from the stripped trunk surface may affect the water balance and tree productivity. To evaluate the effect of bark-stripping, fluorescence emission and stomatal conductance of leaves were determined in groups of barkstripped and control trees. Fv/Fm ratio was found to be significantly lower in bark-stripped trees indicating a reduced photosynthetic efficiency of PSII. Photosynthesis was not found to be stomata limited. The reduction in Fv/Fm resulted from a decline in maximum and variable fluorescence while the initial fluorescence of the darkadapted state (Fo) remained constant. A general decline in photosynthetic efficiency of PSII was found in all trees during the summer, probably reflecting the prolonged environmental stresses during a hot and dry season. Additional stress caused by the bark-stripping seems to enhance the susceptibility to photoinhibition of the trees.
Keywords: bark-stripping; fluorescence emission; Quercus Suber L; water relations

Impacte do Platypus cylindrus F.(Coleoptera, Platypodidae) en Quercus suber L - Ferreira, M. C.; Ferreira, G. W. S. (Scientia gerundensis, 1992)
The main symptoms of attacked trees by Platypus cylindrus F. are given. Data on bioecology, dispersion and impact of this species on Quercus suber L. are presented. Protection mesures.
Keywords: Cork oak; Platypus cylindrus F.; Quercus Suber L